P211 Assessment of operability in early stage lung cancer: results from the national lung cancer audit. (16th November 2010) - Woolhouse, I; Stanley, R; Beckett, P; Peake, M D
Abstract : Background: NICE guidelines recommend that patients who are staged as candidates for curative treatment on CT should undergo further evaluation with PET scan, mediastinal sampling (where appropriate) and lung function tests to confirm stage and to assess fitness for surgery. Under-use and/or variability in the interpretation of these investigations as well as the frequency of co-morbidities may contribute to the relatively low surgical resection rates seen within England. These data are collected by the national lung cancer audit but have not previously been reported at a national level. Methods: Data are presented for patients submitted to the national lung cancer audit with histologically confirmed non-small lung cancer (NSCLC) first seen in England in 2008. It is anticipated that data for 2009 will be available for presentation at the meeting. Results: 13 488 patients (53%) had histologically confirmed NSCLC of which staging data were available for 11 661 patients. 2071 (18%) had stage I or II disease. Investigations and treatment for these patients are shown in the Abstract P211 Table 1 42% of patients with stage I disease who did not undergo surgery had good performance status (WHO 0-1) and adequate FEV1 for lobectomy (>1.5L). 23% of patients with stage II disease who did not undergo surgery had good performance status and adequate FEV1 for pneumonectomy (>2.0L). Conclusion: PET scanning is generally being performed as recommended in national guidelines. The low level of recording of lung function may represent poor data completeness for this field or, more worryingly, under use of this test. The available spirometric data suggest that lung function is relatively well preserved in this group of patients. In particular, approximately one third of those patients who did not undergo surgery appeared to have adequate respiratory reserve and performance status to tolerate resection. The reasons why these patients did not undergo surgery require further evaluation at a local level.